2013
DOI: 10.1007/s00232-013-9591-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fatal Carbon Monoxide Poisoning on the Surface Charge of Blood Cells

Abstract: The objective of this investigation was to evaluate postmortem changes of electric charge of human erythrocytes and thrombocytes after fatal carbon monoxide (CO) poisoning. The surface charge density values were determined on the basis of the electrophoretic mobility measurements of the cells carried out at various pH values of electrolyte solution. The surface charge of erythrocyte membranes after fatal CO poisoning as well as after sudden unexpected death increased compared to the control group in the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
(25 reference statements)
1
6
0
2
Order By: Relevance
“…The results of the present experiment showed that CO poisoning increases the difference in RBC sizes in the blood, weakens the elastic deformation and O 2 carrying capacities of RBCs, and causes cellular hypoxia. These findings are supported by other studies (Szeremeta et al 2013). In the present study, Hb and the morphology and sizes of RBC recovered after the CO-poisoned rats were treated with HBO therapy.…”
Section: Hbo Alleviated the Hypoxia Condition In Co-poisoned Ratssupporting
confidence: 92%
“…The results of the present experiment showed that CO poisoning increases the difference in RBC sizes in the blood, weakens the elastic deformation and O 2 carrying capacities of RBCs, and causes cellular hypoxia. These findings are supported by other studies (Szeremeta et al 2013). In the present study, Hb and the morphology and sizes of RBC recovered after the CO-poisoned rats were treated with HBO therapy.…”
Section: Hbo Alleviated the Hypoxia Condition In Co-poisoned Ratssupporting
confidence: 92%
“…Exposure to CO can lead to toxicity; it is absorbed through the lungs and reacts with the hemoglobin in red blood cells by binding to iron with 200 times higher affinity than O 2 . The complex formed is known as carboxyhemoglobin (COHb) . As most CO remains in the blood, the COHb percentage saturation (%COHb) acts as an estimate and a guide to help determine exposure levels .…”
Section: Effects Of Co In Humans According To %Cohbmentioning
confidence: 99%
“…Сильные последствия могут возникнуть в связи с нарушениями не только газообмена, но и формы и размеров клеток. Появление HbCO может повредить основные метаболические пути, которые отвечают за нормальную функцию гемоглобина и целостность клеточной мембраны [9]. В результате это может стать причиной сближения эритроцитов и образования агрегатов (см.…”
Section: Discussionunclassified
“…Наряду с этим воздействие СО на кровь вызывает повреждение клеточной мембраны, изменяется поверхностный заряд эритроцитов [9]. К важным патогенным эффектам воздействия СО на кровь относится повышенная склонность к тромбозам [10].…”
unclassified